Audience engagement in the discourse of TV news kernels: The case of BBC News at Ten. Issue 2 (April 2020) - Feng, Debing
Existing studies have extensively explored audience engagement in TV news, but not enough attention has been paid to the discursive (re)presentation of this phenomenon in the discourse of TV news kernels. Based on a pool of news items collected from BBC News at Ten, this article aims to investigate how the discourse of news kernels is constructed and presented to engage the audience. The analysis shows that news values and (simulated) journalist–audience interaction are two main ways employed by the journalists to achieve audience engagement in presenting TV news kernels. On one hand, a news kernel tends to cover the most newsworthy information of the news story, and the news text; on the other hand, it is often styled as newsworthy, too. In the meanwhile, the presentation of the news kernel tends to create a sense of (simulated) interaction between the journalist and the audience by practices such as pre-opening remarks, introducing the reporter and alerting the audience, among others. The findings reflect quite different journalistic practice of TV news kernels from that of print news leads.